Knowledge and attitudes of Latin American gynecologists regarding unplanned pregnancy and use of combined oral contraceptives - Bahamondes L; Lira-Plascencia J; Martin R; Marin V; Makuch MY (Dove Medical Press, 2015)
Luis Bahamondes,1 Josefina Lira-Plasencia,2 Ricardo Martin,3 Victor Marin,4 Maria Y Makuch1 1Department of Obstetrics and Gynecology, School of Medical Sciences, University of Campinas (UNICAMP), Campinas, Brazil; 2Instituto Nacional de Perinatología, México, DF, México; 3Hospital Universitario, Fundación Santa Fe de Bogotá, Bogotá, Colombia; 4Hospital Central, Petróleos Mexicanos, México, DF, México Background: Unintended pregnancy is a public health problem and unmet medical need worldwide. It is estimated that in the year 2012, almost 213 million pregnancies occurred, and the global pregnancy rate decreased only slightly from 2008 to 2012. It was also estimated that 85 million pregnancies (40% of all pregnancies) were unintended and that 38% ended in an unintended birth. Objectives: To assess knowledge and attitudes of Latin American (LA) obstetricians and gynecologists (OBGYNs) regarding unintended pregnancies and aspects of combined oral contraceptive (COC) use. Methods: A survey was conducted during a scientific meeting about contraception in 2014, in which OBGYNs from 12 LA countries who provide attention in contraception were invited to respond to a multiple-choice questionnaire to assess their knowledge and attitudes regarding unplanned pregnancy and some aspects regarding COC use. Results: A total of 210 OBGYNs participated in the study. Their knowledge regarding COC failure was low. The participants reported they believed that their patients habitually forgot to take a pill and that their patients did not know what to do in these situations. They were aware of the benefits of COC use; however, they were less prone to prescribe COCs for the purpose of protecting against ovarian and endometrial cancer, and one-quarter of them had doubts about the association between COC use and cancer risk. Conclusion: The interviewed LA OBGYNs showed some flaws in terms of knowledge of COC failure rates and the non-contraceptive benefits and risks of COCs. To adequately counsel their patients regarding COC intake, OBGYNs must be updated regarding all aspects of COC use. Keywords: contraception, unintended pregnancy, benefits of oral contraceptives